Analysis of Students’ Grammatical Errors in Writing Descriptive Text at First Grade Students of SMAN 5 Kabupaten Tangerang in Academic Year 2018/2019 - Citra Ayu Ningthias; Agus Mulyana (Foremost Journal, 2020)
ABSTRACTThis research was conducted in order to find out what kinds of grammatical errors frequently committed by first grade students of SMAN 5 Kabupaten Tangerang in Academic Year 2018/2019. The population of this research was the first grade students of SMAN 5 Kabupaten Tangerang. In selecting the sample, the writer used purposive sampling technique. The sample of this research was students of X MIPA 1 class which consisted of 36 students. In conducting this research, the writer used qualitative research method. Moreover, the instrument used for this research was an essay test which was about writing a descriptive text in order to collect the data of students‟ grammatical errors in writing descriptive text. The result of this research shows that the students committed some grammatical errors in writing descriptive text, especially in the use of adjectives, adverbs, articles, nouns, pronouns, preposition, and verbs. Based on the result, the error in use of verbs is the most common errors in students‟ descriptive text writing products. Keywords: Descriptive Text, Error Analysis, Grammatical Error, Writing